Aplikasi Packet Diffusion Model untuk Menganalisis Pengaruh Fenomena Micromixing terhadap Jalannya Reaksi Kimia Paralel di dalam Reaktor Tangki reraduk Kontinyu dengan Aliran Umpan Terpisah - Ali Altway; Sugeng Winardi; M Rachimoellah (Faculty of Engineering, Universitas Gadjah Mada, 2004)
The effect of turbulent mixing on the course of two fast parallel competitive chemical reactions (netralization of sodium biborate snd iodide-iodate oxidation-reduction reactions) carried out in continuous stiwed tank reaktors have been studied theoretically, using PacketDiffusion Model, and experimentally to validate the theoretical predictions.System studied consists of flat bottom cylindrical tank 0.2 m in diameter. The height of liquid in the tank is also 0.2 m. The tank was equipped with Fan Turbine with diameter equal to I/3 tank diameter. Sulphuric acid solution (0.5 Il,Q was fed into the tank through 2 mm-diameter pipe, and the aquous solution containing 0.0909 M NaH2Boj, 0.0909 M H:Bo:, 0.0116667 M KI, and 0.0023333 M KIO3wasfed into the tank through I0 mm-diameter pipe. The rate of acid solution was varied 0,045, 0.068, and 0.09 liter/minute, while the rate of the other solution was varied I, 1.5, and 2 liter/minute (the rate variation coruespond to the mean residence time variation of 6, 4, and 3 minutes). The impeller rotation speedwas varied; 9,12, and I5 rps. The iodine concenftation in the tank influent was analyzed using spectrophotometer.The simulation works conclude that the selectivity of iodine decrease with increasing impeller rototion speed for the mean residence time of 3 and 4 minutes, while for the mean residence time of 6 minutes, the iodine selectivity increase with increasing impeller rotation speed. Increasing the mean residence time from 3 to 4 minutes will decrease the iodine selectivity, while increasing the mean residence time further to 6 minutes will increase the selectivity. The theoretical prediction using Packet Difusion Model agree fairly well with the experimental data. The experimental studies also showed that the feed position in the region of high turbulent intensity (impeller region) give lower iodine selectivity compaired to the selectivity in the region of lower turbulent intensity. The Packet Dffision Model cannot simulate the effect offeed position on the iodine selectivity.Keywords: Packet Diffusion Model, Micromixing, and Continuous Stirred Tank Reactor